POLA-POLA JALUR PADA PATH ANALISYS UNTUK ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI UN SMA DI KABUPATEN LUMAJANG - Isdarmawan, Agus; Tirta, I Made; Dewi, Yuliani Setia (Department of Mathematics Education , University of Jember, 2013)
Abstract. Path analysis is a technique to analyze the effect of free and bound variables in which every variable correlates or associates with cause and effect directly or indirectly. This study was conducted to determine some factors which influenced National Examination at Senior High School in Lumajang. The Data were analyzed using path analysis. The results of the study were explained as follows: 1. The correlation of variables in path analysis followed the pattern of direct, indirect and mixed. 2. Path analysis could be applied to the analysis of the relationship between exogenous variables (Practical Training (X1), Assignment (X2), and Daily Test (X3)) with endogenous variables (Mid-Term Test (Y1), Final-Term Test (Y2), and National Examination (Z)). Daily Test (X3) contributed directly to Mid-Term Test (Y1). On the other hand, Practical Training (X1) and Daily Test (X3) did not contribute significantly to the Final-Term Test (Y2). 3. Assignment (X2) has direct and indirect influence on National Examination (Z) through Final-Term Test (Y2). 4. Daily Test (X3) did not have a direct influence to Final-Term Test (Y2) but it had a direct impact either through National (Z or through Mid-Term Test (Y1) and Final-Term Test (Y2) which contributed 19.6% of the total site. The direct contribution of Mid-Term Test (Y1) to National Examination (Z) was the highest direct contribution in this study with 40% of the total site. While, the contribution of Practical Training (X1), Assignment (X2), Daily Test (X3), Mid-Term Test (Y1), and Final-Term Test (Y2) simultaneously influenced National Examination (Z) with 93.5% . Abaut 6.5% was influenced by the other factors which could not be described in this study. Key Words : National Examination, Path Analysis, Variable Exogenous, endogenous variables